Reptile species composition at three forest reserves in the Central Forest Spine ecological corridor B-SL1, Selangor, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Central Forest Spine (CFS) is an important initiative to reconnect fragmented forest areas in the Peninsular Malaysia. According to the master plan (PIRECFS 2022), 39 ecological corridors have been identified, including CFS B-SL1, which connects Raja Musa Forest Reserve, Bukit Tarek Forest Reserve, and Gading Forest Reserve in Selangor. A review of existing research on reptilian diversity in these reserves revealed a lack of studies, with some focusing on the Bukit Tarek Forest Reserve. This study aims to document the reptile species present in CFS B-SL1. Fieldwork was conducted in May, June, August, September, and October 2022, with two sampling sessions in each forest reserve. A total of 25 pitfall traps were used for five consecutive nights, and active searches were done for two nights per session. The study identified 18 species from nine families, with Calotes emma being the most frequently captured species (n=31). Gading Forest Reserve constitutes the highest number of species (12 sp). The Agamidae family accounted for the highest families in B-SL1, which is 65.08%. Jaccard’s similarity dendrogram indicated Gading Forest Reserve and Raja Musa Forest Reserve clustered together, although the similarity was below 0.4. Kruskal-Wallis test indicated no significant difference in reptile diversity across three forest reservesThe rarefaction curve indicates that more species could be discovered if the sampling effort were increased. Recommendation includes proposing buffer zones at the corridor and monitoring the usage of herbicides at the plantations within the corridor. The study suggests that more time and effort are needed to uncover additional reptilian species in these forest reserves.
Keywords: Central Forest Spine; Selangor, reptiles; herpetofauna; conservation